Transcriptome and metabolome analyses provide crucial insights into the adaptation of chieh-qua to Fusarium oxysporum infection - Qiao, Yanchun; Peng, Jiazhu; Wu, Bei; Wang, Min; He, Guoping; Peng, Qingwu; Gao, Yin; Liu, Yuping; Yang, Songguang; Dai, Xiuchun (Frontiers in Plant Science, 2024)
Chieh-qua (Benincasa hispida Cogn. var. Chieh-qua How) is a wax gourd variety that is generally susceptible to infection and damage by Fusarium oxysporum during its cultivation. Therefore, analyzing the adaption mechanism of chieh-qua to F.Oxysporum infection is of great significance for cultivating resistant varieties.Through comparative transcriptome analysis between F. Oxysporum infected samples and control samples of susceptible lines, this study found that proteins such as NPR1, TGA and PR1 in plant hormone signal transduction pathway were up-regulated after infection, which may activate a series of plant secondary metabolic synthesis pathways. In addition, the expression of 27 genes in the flavonoid biosynthetic process in resistant lines after infection was significantly higher than that in susceptible lines, indicating that these genes may be involved in fungal resistance.This study also found that alternative splicing of genes may play an important role in responding to F. Oxysporum infection. For example, plant protein kinase genes such as EDR1, SRK2E and KIPK1 were not differentially expressed after F. Oxysporum infection, but the transcripts they produced differ at the transcription level. Finally, through comparative metabolome analysis, this study identified potentially functional substances such as oxalic acid that increased in content after F. Oxysporum infection.Through integrated analysis of transcriptome and metabolome, some differential expressed genes significantly related to differential metabolites were also identified.This study provides a basis for understanding and utilizing chieh-qua's infection mechanism of F. Oxysporum through analysis of the transcriptome and metabolome.